Arabidopsis pathology breathes new life into the necrotrophs-versus-biotrophs classification of fungal pathogens - Oliver, Richard; Ipcho, S. (2004)
Fungal plant pathologists have for many decades attempted to classify pathogens into groups called necrotrophs, biotrophs and, more recently, hemibiotrophs. Although these terms are well known and frequently used, disagreements about which pathogens fall into which classes, as well as the precise definition of these terms, has conspired to limit their usefulness. Dogmas concerning the properties of the classes have been progressively eroded. However, the genetic analysis of disease resistance, particularly in the model plant Arabidopsis thaliana, has provided a biologically meaningful division based on whether defence against fungal pathogens is controlled via the salicylate or jasmonate/ethylene pathways. This mode-of-defence division distinguishes necrotrophs and biotrophs but it limits the biotroph class to pathogens that possess haustoria. The small number and limited range of pathogens that infect Arabidopsis means that several interesting questions are still unanswered. Do hemibiotrophs represents a distinct class or a subclass of the necrotrophs? Does the division apply to other plant families and particularly to cereals? and does this classification help us understand the intricacies of either fungal pathogenicity or plant defence?